Novel coumarin derivatives as potent acetylcholinesterase inhibitors: insight into efficacy, mode and site of inhibition. Issue 7 (3rd May 2019) - Baruah, Prayasee; Basumatary, Grace; Yesylevskyy, Semen O.; Aguan, Kripamoy; Bez, Ghanashyam; Mitra, Sivaprasad
Abstract : The inhibitory efficacy of two substituted coumarin derivatives on the activity of neurodegenerative enzyme acetylcholinesterase (AChE) was assessed in aqueous buffer as well as in the presence of human serum albumin (HSA) and compared against standard cholinergic AD drug, Donepezil (DON). The experimental data revealed the inhibition to be of non-competitive type with both the systems showing substantial inhibitory activity on AChE. In fact, one of the tested compounds Chromenyl Coumarate (CC) was found to be better inhibitor (IC50 = 48.49 ± 5.6 nM) than the reference drug DON (IC50 = 74.13 ± 8.3 nM), unequivocally amplifying its importance. The structure of the compound was found to play a vital role in the inhibitory efficiency, validating previous Structure Activity Relationship (SAR) reviews for coumarin. The mechanism of inhibition remained impervious when the experimental medium was switched from aqueous buffer to HSA, albeit noticeable change in the inhibition potency of the compound 3, 3′- Methylene-bis (4-hydroxy coumarin) (MHC) (38%) and CC (35%). Both the coumarin derivatives were observed to bind to the peripheral anionic site (PAS) of AChE and also found to displace the fluorescence marker thioflavinT (ThT) from AChE binding pocket. All experimental observations were seconded by molecular docking and MD simulation results. The inferences drawn in this study form a foundation for further investigation on these compounds; magnifying the probability of their usage as AD drugs and re-emphasizes the significance of drug delivery media while considering the inhibition potencies of targeted drugs.